Ultradeep Imaging of Nearby Dwarf Irregular Galaxies: Young Objects in the Far Outer Disk - Deidre A. Hunter; Hong-Xin Zhang; Bruce G. Elmegreen; Ella R. Castelloe; Hannah Michaye Ledford; Ishara Nisley; Ryuga Hatano (The Astronomical Journal)
Ultradeep UBVI imaging of 10 nearby (≤7.8 Mpc) noninteracting dwarf irregular galaxies are used to examine their far outer stellar disks. The annulus between 26 mag arcsec ^−2 and 29 mag arcsec ^−2 in the V band is what we define as the far outer disk and is our focus here. Photometry of distinct objects in the far outer disks, including far-UV images, is used to determine ages of the objects in order to look for those that are young. In three of the galaxies we find objects with high-confidence ages ≤30 Myr. These objects are too young to have scattered into the far outer disk from the central regions. Therefore, they likely formed in situ. How star-forming gas clouds formed in the extreme environment of the outer stellar disks of dwarfs is a primary unanswered question.